PENANAMAN NILAI-NILAI TASAWUF DALAM KELUARGA - st rahmah (UIN Antasari Banjarmasin, 2017)
Family is a small community in society. Every Muslim is required to live in order to live the demands of Islamic teachings. The family is the most important unit for the development process of the ummah. a good personality is formed from a family that instills good manners. The concept of family in Islam is quite clear even Islam is very priority of individual and family coaching. Because the family is a good prerequisite for a nation and Country, especially if all families follow the guidelines submitted religion, in addition the family is also the closest environment with children, since children are born, in this family the children will have much experience to grow and developing for the future. Inside the family parents can give examples of behaviors that will be imitated by children, because in the family is the most effective place to membelajarkan value of religion to the child. The role of parents in the family as guides, caregivers, teachers, mentors, and example in the family. Parents are very big role in inculcating the values of Sufism as the foundation of his children, With the inculcation of the values of mysticism by parents, it is expected that in the next stage of development the child will be able to distinguish good bad, right wrong, so that children can apply it in everyday life